Optimizing E-Commerce For Micro Small Medium Enterprises - Danang Adi Putra; Indah Oktari Wijayanti; Herawansyah Herawansyah (Universitas 45 Surabaya, 2024)
Technological advances to support the excellence of a company need to be carried out with policies that focus on marketing methods in the company, one of which is through e-commerce. In connection with that, business people in companies tend to want effective and efficient marketing as a means of information in transactions. MSMEs (Micro, Small and Medium Enterprises) are new in commercial activities or activities. These MSMEs are engaged in a trade where, in this case, it involves entrepreneurial activities or activities. Conventional business activities, which in recent years have become the spearhead of driving the country's economic growth, must immediately transform into a technology and information-based business mode or what is commonly called Online Business. Online business is a system or business activity that relies on the Internet as a marketing medium. Online sales or Online Business have many advantages over conventional sales. Therefore, it is necessary to have knowledge, understanding and skills in managing a business online. Observing the problems mentioned above, training is needed for MSMEs to understand how to run a business online, as well as skills in managing their business online by utilizing various social media and e-commerce features available.